The roles of acquired and innate immunity in human T-cell leukemia virus type 1-mediated diseases - Kannagi, Mari; Hasegawa, Atsuhiko; Takamori, Ayako; Kinpara, Shuichi; Utsunomiya, Atae (Frontiers in Microbiology, 2012)
Human T-cell leukemia virus type 1 (HTLV-1) causes adult T-cell leukemia (ATL) and HTLV-1-associated myelopathy/tropical spastic paraparesis in small subsets of HTLV-1-carriers. HTLV-1-specific T-cell responses play critical roles in anti-viral and anti-tumor host defense during HTLV-1 infections. Some HTLV-1-carriers exhibit selective loss or anergy of HTLV-1-specific T-cells at an asymptomatic stage. This is also observed in ATL patients and may therefore be an underlying risk factor of ATL in combination with elevated proviral loads. HTLV-1-specific T-cells often recognize the viral oncoprotein Tax, indicating expression of Tax protein in vivo, although levels of HTLV-1 gene expression are known to be very low. A type-I interferon response can be induced by HTLV-1-infected cells and suppresses HTLV-1 expression in vitro, suggesting a role of type-I interferon response in viral suppression and pathogenesis in vivo. Both acquired and innate immune responses control the status of HTLV-1-infected cells and could be the important determinants in the development of HTLV-1-mediated malignant and inflammatory diseases.